EU corporate R&D intensity gap: What has changed over the last decade? - Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2016)
This paper contributes with new findings to the literature on corporate research and development (R&D) intensity decomposition by examining the effects of several parameters on R&D intensity and investigating its comparative distribution among top R&D firms, sectors and world regions/countries. It draws on a longitudinal company-level micro-dataset from 2005 to 2013, and uses both descriptive statistics and decomposition computation methods. The results confirm the structural nature of the EU R&D intensity gap. In the last decade the gap between the EU and the USA has widened, whereas the EU gap with Japan and Switzerland has remained relatively stable. The study also uncovers differences in R&D intensity between EU and US companies operating in the sectors more responsible for the aggregate R&D intensity gap. In contrast, the BRIC (Brazil, Russia, India and China) and Asian Tiger countries (Hong Kong, Singapore, South Korea and Taiwan) R&D intensity gap compared to the EU has remained relatively stable, while companies from the rest of the world are considerably reducing such gap. Finally, the study shows a high concentration - sustained over time - of R&D investment in a few countries, sectors and firms, but in the EU there are fewer smaller top R&D firms that invest more intensively in R&D, than in the most closed competing countries.
Keywords: O30; O32; O38; O57; 330; corporate R&D; decomposition; EU R&D intensity gap; EU R&D policy